Effect of cataract surgery on retinal nerve fiber layer thickness parameters using scanning laser polarimetry (GDxVCC) - Dada Tanuj; Behera Geeta; Agarwal Anand; Kumar Sanjeev; Sihota Ramanjit; Panda Anita (Indian Journal of Ophthalmology, 2010)
Purpose: To study the effect of cataract extraction on the retinal nerve fiber layer (RNFL) thickness, and assessment by scanning laser polarimetry (SLP), with variable corneal compensation (GDx VCC), at the glaucoma service of a tertiary care center in North India. Materials and Methods: Thirty-two eyes of 32 subjects were enrolled in the study. The subjects underwent RNFL analysis by SLP (GDx VCC) before undergoing phacoemulsification cataract extraction with intraocular lens (IOL) implantation (Acrysof SA 60 AT) four weeks following cataract surgery. The RNFL thickness parameters evaluated both before and after surgery included temporal, superior, nasal, inferior, temporal (TSNIT) average, superior average, inferior average, and nerve fiber index (NFI). Results: The mean age of subjects was 57.6 ± 11.7 years (18 males, 14 females). Mean TSNIT average thickness (μm) pre- and post-cataract surgery was 49.2 ± 14.1 and 56.5 ± 7.6 ( P = 0.001). There was a statistically significant increase in RNFL thickness parameters (TSNIT average, superior average, and inferior average) and decrease in NFI post-cataract surgery as compared to the baseline values. Mean NFI pre- and post-cataract surgery was 41.3 ± 15.3 and 21.6 ± 11.8 ( P = 0.001). Conclusions: Measurement of RNFL thickness parameters by scanning laser polarimetry is significantly altered following cataract surgery. Post the cataract surgery, a new baseline needs to be established for assessing the longitudinal follow-up of a glaucoma patient. The presence of cataract may lead to an underestimation of the RNFL thickness, and this should be taken into account when analyzing progression in a glaucoma patient.